KEMAJUAN TEKNOLOGI 5G MEMPERCEPAT ADOPSI DAN INOVASI IOT TERHADAP PENDIDIKAN DI PERGURUAN TINGGI - Unan Yusmaniar Oktiawati; Ernawita; Syamsul Anwar; Ali Ramatni; Jacobus Wiwin Kuswinardi; Joni Wilson Sitopu (EDU RESEARCH, 2024)
This article presents a literature review on the impact of 5G technology advancements in accelerating Internet of Things (IoT) adoption and innovation in educational environments, particularly in higher education. 5G technology has brought significant changes in the digital ecosystem, offering faster, more reliable, and efficient connectivity. This literature review explores how 5G technology has driven the acceleration of IoT adoption and innovation in higher education in various aspects, such as teaching and learning, campus management, student services, and research and development. The review identifies several key benefits of 5G-enabled IoT integration in higher education, including improved operational efficiency, personalised services, increased student engagement, optimised use of resources, and improved research and development quality. However, this review also reveals the challenges that must be faced in implementing 5G-based IoT solutions, such as security issues, data privacy, and infrastructure readiness and human resource competencies. The conclusion of this literature review highlights that advances in 5G technology have accelerated IoT adoption and innovation in higher education, opening up significant digital transformation opportunities in the higher education ecosystem. However, strategic and comprehensive planning is required to optimise the potential of 5G-based IoT and overcome the challenges that come with it